The examination of factors influencing the recognition of affective states associated with tennis players' non-verbal behaviour. (July 2022) - Fritsch, Julian; Preine, Leon; Jekauc, Darko
Abstract: In tennis, the non-verbal behaviours shown after a rally may indicate the affective state of players. The purpose of the present study was to assess whether (a) the point outcome, (b) the duration of video-excerpts, and (c) the tennis expertise of the participants would influence the recognition rates of the affective state. To that end, 115 participants were shown non-verbal behaviour of tennis players after a point and asked to rate whether the player had just won or lost a point. The results indicate that the recognition rates were higher for lost than for won points. Moreover, participants who were members of a tennis club had a higher recognition rate. Finally, there was no difference in the recognition rate regarding the duration of video excerpts. The findings point to a negativity bias and the bio-cultural framework in relation to the recognition of affective states associated with non-verbal behaviour. Highlights: Recognition assessed for affective states associated with non-verbal behaviour. Higher recognition rates of affective states after a lost than after a won point. Members of tennis clubs have higher recognition rates of affective states. Duration of video excerpts has no effect on recognition rates of affective states.